Study on the Dynamic Performance of Planetary Gear Transmission System of the MW Level Wind Power Speed-growth Gearbox - Wang Chunguang (Jixie chuandong)
The load sharing planetary gear speed-growth train for wind power generator is studied,which is composed of two stage planetary gear and one stage plane gear.The influence of external load excitation and time varying mesh stiffness is considered,and the system dynamics model including radial and torsion is deduced in detail.The dynamic mesh force between planet gear and sun gear and annular gear ring are analyzed.The radial velocity and torsional vibration angular velocity change on the central components of two stage planetary gear and the mesh force characteristics are obtained.This provides theoretical basis for the dynamic optimization design of the load sharing planetary gear speed-growth train.